The Role Of Healthcare Team In Promoting Health Equity: A Systematic Review (Journal of Namibian Studies : History Politics Culture, 2022)
Background: Health equity remains a critical global challenge, with disparities in access to healthcare and health outcomes persisting across regions and populations. Understanding the role of healthcare teams in promoting health equity is essential for designing effective interventions and policy frameworks to address these disparities. Aims: This systematic review examines health equity policies, strategies, and interventions, focusing on the role of the healthcare team in promoting health equity.Method: The review, which included eleven studies published between 2018 and 2022, aimed to classify necessary research from databases like PsycINFO, MEDLINE, and Web of Science. Key themes included incorporating a health equity lens in public policies, strategies for achieving health equity within healthcare systems, and identifying priority areas for health research.Results: Synthesis of findings revealed several key themes, including the incorporation of health equity into public policies, strategies for achieving health equity within healthcare systems, research priorities for addressing health disparities, and interventions targeting specific health domains such as oral health in children and the integration of social determinants of health into medical education curricula.Conclusion: The findings underscore the importance of policy integration, strategic interventions, and research prioritization in promoting health equity within healthcare systems. Recommendations include prioritizing health equity in policy-making, building structural competency within healthcare teams, and addressing social determinants of health to foster equitable healthcare practices both locally in Saudi Arabia and internationally. However, limitations include the reliance on existing literature and potential lack of generalizability across diverse contexts.